Macrophage metallothioneins participate in the antileishmanial activity of antimonials - Vargas, Deninson Alejandro; Gregory, David J.; Koren, Roni Nitzan; Zilberstein, Dan; Belew, Ashton Trey; El-Sayed, Najib M.; Gómez, María Adelaida (Frontiers in Parasitology, 2023)
Host cell functions that participate in the pharmacokinetics and pharmacodynamics (PK/PD) of drugs against intracellular pathogen infections are critical for drug efficacy. In this study, we investigated whether macrophage mechanisms of xenobiotic detoxification contribute to the elimination of intracellular Leishmania upon exposure to pentavalent antimonials (Sb V ). Primary macrophages from patients with cutaneous leishmaniasis (CL) (n=6) were exposed ex vivo to L. V. panamensis infection and Sb V , and transcriptomes were generated.Seven metallothionein (MT) genes, potent scavengers of heavy metals and central elements of the mammalian cell machinery for xenobiotic detoxification, were within the top 20 upregulated genes. To functionally validate the participation of MTs in drug-mediated killing of intracellular Leishmania, tandem knockdown (KD) of MT2-A and MT1-E, MT1-F, and MT1-X was performed using a pan-MT shRNA approach in THP-1 cells. Parasite survival was unaffected in tandem-KD cells, as a consequence of strong transcriptional upregulation of MTs by infection and Sb V , overcoming the KD effect. Gene silencing of the metal transcription factor-1 (MTF-1) abrogated expression of MT1 and MT2-A genes, but not ZnT-1. Upon exposure to Sb V , intracellular survival of Leishmania in MTF-1 KD cells was significantly enhanced. Results from this study highlight the participation of macrophage MTs in Sb-dependent parasite killing.